IMPLEMENTASI MODEL BLENDED LEARNING DALAM PEMBELAJARAN PPKN DI SDN BONOROWO KABUPATEN KEBUMEN TAHUN AJARAN 2020/2021 - Chairiyah Chairiyah; Nadziroh Nadziroh; Wachid Pratomo (Cerdas Proklamator, 2021)
This article aims to describe the implementation of the blended learning model in PPKn learning in grade 1 SD N Bonorowo Kebumen. The type of research used is descriptive qualitative. Data collection techniques using observation, interviews and documentation. The data analysis technique used the Miles and Huberman model, namely data collection, data reduction, data presentation and conclusion drawing. The validity of the data was done by increasing the persistence and triangulation techniques. The results showed that 1) The implementation of the blended learning model in PPKn learning was carried out well starting with face-to-face followed by online, using the same tools as other models, using learning video media and concrete media that could activate students, 2) The supporting factor was assistance. quota from the government, the existence of a library, the existence of a private room that can be used as a temporary class, and parents can access a smartphone, 3) The inhibiting factors are signals and devices that are less supportive, 4) Solutions to overcome these inhibiting factors are easy access to wifi, assignment manuals, and providing screenshots of the learning videos. Keywords: Implementation, Blended Learning Model, PPKn Learning